Estudo prospectivo e econômico da substituição do chuveiro elétrico pelo aquecedor solar na cidade de Uberlândia-MG - Dias, Lucilene Silva (2005)
This work shows the results of a field research concerning the substitution of the electric shower by the solar water heater made in the city of Uberlândia. The objective of this work is to study some items related to the use of solar technology for water heating. These items are covered with many subjects like: professionals that work in the area like engineers and architects, the ordinary citizen and users of water solar heater. The advantages of the solar water heating systems over the electric shower are shown, in terms of load side management as well as demand side management. An economic return on investment comparison is made between the two alternatives for water heating, with special attention given to the electric energy tariff cost of residential consumers. The specific time for the return on investment as well as the economy obtained during the life cycle of solar heater is shown.